Effects of nitrogen supply rate on photosynthesis, nitrogen uptake and growth of seedlings in a Eucalyptus/Dalbergia odorifera intercropping system. (26th September 2021) - Yao, X.; Lan, Y.; Liao, L.; Huang, Y.; Yu, S.; Ye, S.; Yang, M.
ABSTRACT: The introduction of N2 ‐fixing species into a Eucalyptus plantation resulted in a successful planting system. It is essential to understand the contribution of nitrogen (N) competition and photosynthetic efficiency to plant dry matter yield to shed more light on the growth mechanism of the Eucalyptus/ legume system. We compared N competition, photosynthesis and dry matter yield of Eucalyptus urophylla × E . grandis and the N2 ‐fixing tree species Dalbergia odorifera in intercropping and monoculture systems under different N levels. The photosynthesis of E. urophylla × E. grandis was improved, while that of D. odorifera was inhibited in the intercropping system. Intercropped E. urophylla × E. grandis increased the N utilization and the dry matter yield by 6.57–48.46% and 7.59–97.26%, and decreased those of D. odorifera by 10.21–30.33% and 0.48–13.19%, respectively. Furthermore, N application enhanced the competitive ability of E. urophylla × E. grandis relative to D. odorifera and changed the N contents and chlorophyll synthesis to optimize the photosynthetic structure of both species. Our results reveal Eucalyptus for photosynthesis, N absorption and increasing the growth benefit from the introduction of N2 ‐fixing species, which hence can be considered to be an effective sustainable management option of Eucalyptus plantations. Abstract : Compared with monoculture, intercropped Eucalyptus improved its own performance, but decreased that of co‐cultivated Dalbergia odorifera, particularly at nitrogen application.